2014
DOI: 10.1007/s00330-014-3538-6
|View full text |Cite
|
Sign up to set email alerts
|

MRI predictors of clinical success in MR-guided focused ultrasound (MRgFUS) treatments of uterine fibroids: results from a single centre

Abstract: • MRgFUS appears to be a valid alternative to other uterus-preserving therapies • Patient selection is a significant factor in achieving high NPV ratios • MRI screening parameters correlate with the amount of fibroid ablation in MRgFUS • NPV results of more than 80 % correlate with higher clinical success rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
71
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(76 citation statements)
references
References 39 publications
4
71
1
Order By: Relevance
“…In another study by Mindjuk et al (15), multivariate analysis revealed that although the nonperfused volume ratio of fibroids characterized by low SI in contrast-enhanced T1-weighted images was significantly high, T2 SI could not effectively predict the same. These two studies show that the T2 SI of a uterine fibroid cannot differentiate between vascularity and water from edema or degeneration (Figs.…”
Section: T1-perfusion Imagingmentioning
confidence: 99%
“…In another study by Mindjuk et al (15), multivariate analysis revealed that although the nonperfused volume ratio of fibroids characterized by low SI in contrast-enhanced T1-weighted images was significantly high, T2 SI could not effectively predict the same. These two studies show that the T2 SI of a uterine fibroid cannot differentiate between vascularity and water from edema or degeneration (Figs.…”
Section: T1-perfusion Imagingmentioning
confidence: 99%
“…The aim of the operation was to remove the non-implanted part of the placenta; the deeply implanted part of the placenta was left in situ, to be absorbed slowly after the HIFU ablation. The average depth of the uterus was 10.36 AE 2.14 cm (range [8][9][10][11][12][13][14][15]. The median volume of any intraoperative blood loss was 20 ml (range 5-400); no blood transfusions were given.…”
Section: Hysteroscopic Operationmentioning
confidence: 99%
“…[9][10][11][12] Some reports on the treatment of PA by HIFU have been published recently, but the risk of haemorrhage and infection when using HIFU alone, is still high. In this study, we utilised USgHIFU combined with curettage guided by hysteroscopy to treat PA patients so that the chance of unexpected haemorrhage and infection from HIFU could be reduced.…”
Section: Introductionmentioning
confidence: 99%
“…NPV ratio, which is highly correlated with clinical success, is significantly higher in fibroids characterized by low signal intensity in contrast-enhanced T 1 weighted fat-saturated MR images and lower in fibroids with septations, with subserosal component and in skin-distant fibroids. 45 An adequate patient and strategy selection, combined with technical advances of the system, may lead to higher clinical success and low complication rate. This kind of experience suggests the need, in each field of MRgFUS application, of building clinical, imaging and technical selection criteria for patients' enrolment.…”
Section: Mrgfus Lessons Learned From Non-musculoskeletal Applicationsmentioning
confidence: 99%